E-077 Laboratory analogs of challenging thromboemboli in acute ischemic stroke. (23rd July 2017) - Chueh, J; Litchman, J; Arslanian, R; Carniato, S; Rex, D; Howk, M; Gounis, M; Puri, A
Abstract : Introduction: Recent meta-analysis of randomized clinical trials has shown that endovascular intervention yields higher rates of revascularization and superior functional outcomes as compared to standard medical therapy in the setting of emergent large vessel occlusion causing stroke. However, there remained approximately 20% patients in whom successful revascularization (mTICI score, 2b or 3) was not achieved after stent-retriever thrombectomy [1, 2]. Revascularization achieved with thrombectomy devices depends in part upon the integration of the thrombus material into the retrieval device. The histologic composition and mechanical properties of thrombi are key determinants of effective thrombus-device interaction. We hypothesize that calcified and fibrin-rich thrombi are stiffer than erythrocyte-rich thrombi; therefore, they may serve as the challenging thrombus models to evaluate thrombus-device interactions, and further aid the design and development of future generations of stent retrievers. The goal of this study is to 1) characterization of thromboemboli retrieved from patients with AIS, and 2) development of thrombus analogs with histologic and mechanical characteristics similar to those of challenging clinical thrombi for thrombectomy device testing. Materials and methods: Thrombi were retrieved from patients with AIS using stent retriever devices. Several technical metrics of the thrombectomy procedure such as number of pass attempts and occurrence of embolic complication were collected. Fifty clinical thrombi collected from twenty nine AIS patients underwent histologic analysis, and nine clinical thrombi were subjected to dynamic mechanical analysis (DMA). Thrombus histology was determined by staining specimens for erythrocytes and fibrin content using the Martius Scarlet Blue technique and performing computerized segmentation and quantitative analysis. During the DMA tests, thrombus stiffness was defined as a function of stress variation over strain. The average stress variation at low strain (E1: 0 to 75% strain) and high strain (E2: 75 to 100% strain) was recorded. The results generated from the clinical samples were used to determine the key components of the challenging thrombus analogs, calcium apatite-rich and fibrin-rich thrombus analogs. Results: Of the twenty nine AIS cases analyzed, fifteen cases required multiple pass attempts. The average histologic composition of the clinical thrombi obtained from cases with more than 1 thrombectomy pass was 26% erythrocyte, 54% fibrin, and 20% mixed, whereas the average histologic composition of all the fifty clinical thrombi analyzed was 33% erythrocyte, 47% fibrin, and 20% mixed. The DMA results demonstrated that the stiffness of the challenging clinical thrombi (E1: 0.00011±0.000076MPa, E2: 0.015±0.0083MPa) was similar to that of the fibrin-rich thrombus analogs (E1: 0.00013±0.000002MPa, E2: 0.011±0.0007MPa). Compared to the fibrin-rich thrombus analogs, addition of calcium apatite increased the stiffness of the thrombus analogs by approximately 5 times. Conclusion: Thrombus analogs with mechanical characteristics similar to those of challenging clinical thrombi were successfully developed. The calcium apatite thrombus analog was found to be stiffer than the fibrin-rich thrombus analog. References: . Saver JL et al: Stent-retriever thrombectomy after intravenous t-PA vs. t-PA alone in stroke. N Engl J Med 2015, 372(24):2285–2295. . Dorn F et al: Endovascular treatment of acute intracerebral artery occlusions with the solitaire stent: single-centre experience with 108 recanalization procedures. Cerebrovasc Dis 2012, 34(1):70–77. Disclosures: J. Chueh: None. J. Litchman: None. R. Arslanian: None. S. Carniato: 5; C; Principal Preclinical Research Associate at Stryker Neurovascular. D. Rex: None. M. Howk: None. M. Gounis: 1; C; research grant supported by Stryker Neurovascular. 2; C; consultant for Stryker Neurovascular. A. Puri: 1; C; research grant suppported by Stryker Neurovascular. 2; C; consultant for Stryker Neurovascular.